2014
DOI: 10.1016/j.actbio.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Tropoelastin: A versatile, bioactive assembly module

Abstract: Elastin provides structural integrity, biological cues and persistent elasticity to a range of important tissues including the vasculature and lungs. Its critical importance to normal physiology makes it a desirable component of biomaterials that seek to repair or replace these tissues. The recent availability of large quantities of the highly purified elastin monomer, tropoelastin, have allowed for a thorough characterization of the mechanical and biological mechanisms underpinning the benefits of mature elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 113 publications
2
111
0
Order By: Relevance
“…[30] [31] Over the past few years, we and others have found that, in vitro, these molecules are not needed for the spatial and temporal elastin assembly of tropoelastin. [9,15,20,26,32,33] This may be due to the fact that elastin is over nine times more abundant than microfibrillar components, and therefore tropoelastin-tropoelastin interactions dominate. [34] The observed tropoelastin and aggregate structures are similar to those found in natural tissues, as evidenced by electron microscopy, which supports the concept of an aggregation unit corresponding to tropoelastin assemblies.…”
Section: Tropoelastin Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…[30] [31] Over the past few years, we and others have found that, in vitro, these molecules are not needed for the spatial and temporal elastin assembly of tropoelastin. [9,15,20,26,32,33] This may be due to the fact that elastin is over nine times more abundant than microfibrillar components, and therefore tropoelastin-tropoelastin interactions dominate. [34] The observed tropoelastin and aggregate structures are similar to those found in natural tissues, as evidenced by electron microscopy, which supports the concept of an aggregation unit corresponding to tropoelastin assemblies.…”
Section: Tropoelastin Assemblymentioning
confidence: 99%
“…[37] By exploring the functional roles of domains by systematically introducing mutations at selected sites across tropoelastin, in concert with SAXS and allied methods including SANS, NMR, and molecular dynamics on these constructs, we have solved the solution structures for the normal and a panel of mutant forms of tropoelastin. [9,10,20,26] In each of the mutant cases, there is altered assembly. This has facilitated mapping of these effects onto specific parts of the molecule, together with comparison of the assembly performance of wild-type and mutant forms in vitro and in concert with elastogenic cells.…”
Section: Tropoelastin Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Tropoelastin is the soluble precursor of the insoluble fibrillar elastin in situ (129). EN is an important protein that impacts lung development predominantly during the alveolar stage.…”
Section: Extracellular Matrix Composition Relevant For Lung Vascularmentioning
confidence: 99%
“…This protein is particularly abundant in the vascular wall, being prominent in the aorta and also in elastic vessels. While cell signaling is directed by tropoelastin through cell-surface interactions [2], specific integrin binding sites have been recently identified in tropoelastin where they drive the attachment and proliferation of fibroblasts, endothelial and endothelial progenitor cells [3][4][5]. Also contained within the tropoelastin sequence are short repeating hydrophobic signaling motifs that are recognized by the elastin binding protein (EBP) and promote cellular chemotaxis and vasorelaxation [6].…”
mentioning
confidence: 99%